The differing predictive values of oestrogen receptor assays for large breast cancers. Issue 805 (November 1992) - Gaskell, D. J.; Hawkins, R. A.; Tesdale, A. L.; Sangster, K.; Chetty, U.; Forrest, A. P.
Abstract : Thirty elderly patients with T3 or T4 breast cancer underwent a wedge biopsy for radioligand-binding assay (RLA) of oestrogen receptor (ER) activity. A second, separate group of 21 elderly patients with T3 and T4 breast cancers underwent fine needle aspiration biopsy (FNA) for immunocytochemical assay of ER (ER-ICA). All the women received tamoxifen as primary treatment and response was assessed by UICC criteria. Tumour ER concentration by RLA was correlated with both response (Spearman's R = + 0.52) and time to progression (R = + 0.76). Nine patients with receptor-rich tumours (> 100 fmol/mg protein) failed to show a response. However, the percentage of cells staining for ER by ER-ICA assay was much more strongly related to the likelihood of response (R = + 0.89); no patient with < 20% cells staining responded. Wedge biopsy and the biochemical determination of ER activity is of limited value in predicting the likely response to tamoxifen; ER-ICA assays on such tumours may be more informative.